PENERAPAN MEDIA LABORATORIUM VIRTUAL PHET PADA MATERI HUKUM OHM UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X-IA 5 SMAN 5 BANDA ACEH - Soewarno S (JURNAL FISIKA EDUKASI, 2015)
Research on the Application of Media Virtual Laboratory Phet To Improve Learning Outcomes Physics At Students In SMA Negeri 5 Banda Aceh aims to determine: (1) the activities of teachers and students, (2) the skills of teachers in managing learning, (3) the results of student learning and (4) the students' responses to the use of Virtual Laboratory PhET media in the learning process. This type of research is the Classroom Action Research (PTK) and the approach used in this research is descriptive statistical approach where the data obtained are then processed using statistical methods and explain again using the word. The subjects were students of class X-IA5 SMAN 5 Banda Aceh the school year 2014/2015, amounting to 32 students. Data collection instruments used in research that observation sheets, tests and questionnaires were analyzed using analysis of all three percentages. The results showed (1) an increase in activity of teachers and students during the learning process, (2) an increase in teachers' skills in managing the learning of the category is becoming a very good (3) the percentage of completeness individual as a whole increased from cycle 1 to cycle 3 is 70% , 79% and 95%, and the percentage of the overall classical ketuntasanan also increased 65%, 80% and 91%. (4) The students' responses tend to be positive where 95% of students said he was happy to use this PhET Virtual Laboratory media in learning. From this research it can be concluded that the application of Virtual Laboratory PhET media can improve student learning outcomes on the subject of Ohm's law. It is recommended that research using Virtual Laboratory PhET media can proceed on other relavan material physics and not only at the high school level but also at the SMP so that the conclusions can apply more generative.